RESPONS PERTUMBUHAN GULMA TUKULAN KELAPA SAWIT (Elaeis guineensis JACQ.) TERHADAP PEMBERIAN BEBERAPA JENIS DAN DOSIS HERBISIDA DI PTPN VIII KEBUN CISALAK BARU - Dewi Hastuti; Rusmana x; Zaenal Krisdianto (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2014)
This research had been conducted to determine the dose response of herbicide mixtures against weeds tukulan palm oil that has been held in PTPN VIII Kebun Cisalak Baru. This study used quantitative and qualitative methods with a Completely Randomized Design where treatment consists of two factors, there are 3 levels ie herbicide Glyphosate (H1), Paraquat (H2), Glyphosate + Paraquat (H3) and 4 levels of herbicide dose of 10 ml/0.5 liters of water (D1), 10 ml/1 liter of water (D2), 10 ml/1.5 liters of water (D3), 10 ml/2 liters of water (D4), which was repeated 3 times and each disc consists of two oil palm fruit oil palm plantations (tukulan) and thus require 36 disks palm and there were 72 experimental unit. Observation parameters include leaf chlorophyll content, leaf color, leaf shape and symptoms of poisoning. The results showed that the chlorophyll content parameter with a mixture of herbicides containing Glyphosate dose of Paraquat 5 ml + 5 ml + 0.5 liters of water have an effect on leaf chlorophyll parameters. Then the mixture of herbicides containing Glyphosate dose of Paraquat 5 ml + 5 ml + 1 liter of water affect the parameters of the symptoms of poisoning. While the herbicide mixture containing 10 ml dose of Paraquat + 0.5 liters of water affects the leaf color parameters.